Effective negotiating : teacher's book - Comfort, Jeremy. (Oxford University Press, 1996)
This book is divided into eight units: Preparing the ground, Setting the Agenda, Establishing positionss, Clarifuing positions, Managing conflict, Making and responding to proposals, Bargaining, and Concluision and agreement.